Class Struggle Seen in Ernest Jones’ Three Selected Poems: The Song of The Poor, The Song The Lower Classes, and A Song for People - Andi Ahmad Fijai; Hat Pujiati; Ikwan Setiawan (JENTERA: Jurnal Kajian Sastra, 2022)
This article discusses class struggle of the working class through Ernest Jones’ three selected poems: The Song of The Poor, The Song of The Lower Classes, and A Song for People in the Industrial Revolution era in England. Industrial Revolution is a shift in goods production from human power into mechanical power. This research uses Michael Riffaterre’s Semiotics of Poetry theory to find out the meaning and significance of the chosen poems and uses some opinions and history as hypogram to portray the class struggle of the workers in Industrial Revolution era. The result of this research shows that these poems articulate the voices of the working class in struggling to get justice against the ruling class. AbstrakArtikel ini membahas tentang perjuangan kelas pekerja di tiga puisi pilihan karya Ernest Jones: The Song of The Poor, The Song of The Lower Classes, dan A Song for People di era Revolusi Industri di Inggris. Revolusi Industri adalah perubahan cara produksi barang yang awalnya menggunakan tenaga manusia menjadi tenaga mekanik. Penelitian ini menggunakan teori Semiotika Puisi oleh Michael Riffaterre untuk mengetahui meaning (makna) dan significance (arti) puisi yang terpilih dan menggunakan beberapa opini dan sejarah sebagai hipogram untuk menggambarkan perjuangan kelas pekerja di era Revolusi Industri. Hasil penelitian ini mengeksplorasi perjuangan para pekerja di era Revolusi Industri. Jones melalui puisinya mengartikulasikan suara-suara kelas pekerja dalam perjuangannya mendapatkan keadilan melawan kelas pengusa.